Education and Training (Diklat)-Based Human Resource Development to Increasing Employee Creativity: Literature Study - Gifari, Firzan; Madhakomala, R (Journal of Advances in Accounting, Economics, and Management, 2023)
The ability to think creatively is one of the most valuable competencies in the 21st century. However, data shows that the creativity of human resources in Indonesia is relatively low to compete globally. To improve creative thinking skills, businesses need to play an active role in developing their human resources. This study aims to examine how human resource development based on education and training can be a means of improving the creative thinking skills of human resources in a company. This research was conducted using a qualitative research method with a literature study approach. The data sources used in this research are 3 books 15 journal and 2 article published from 2016 to 2023. Based on the results of this study, it can be implied that companies need to pay greater attention to the development of their human resources through training, especially training that can develop employees' creative thinking skills. This is important to increase the company's productivity and competitiveness in the era of globalization.